The Influence of Korean Culture on The Lifestyle of Students At Raden Mas Said State Islamic University: Positive and Negative Impacts on Family Education and The Modern Environment - Widianingrum, Nabilla Ayu; Harsono, Harsono (UNIVERSITAS PAKUAN, 2022)
The influence of Korean culture has had a positive impact on the lifestyle of students at Raden Mas Said State Islamic University (UIN), particularly in areas such as fashion, hairstyles, and the adoption of Korean cultural trends. This research aims to investigate the influence of Korean culture on the lifestyle of students at UIN Raden Mas Said. The study employs a quantitative descriptive research method and gathers data by distributing questionnaires to UIN Raden Mas Said students. The results of this research indicate that Korean culture has been well-received by UIN Raden Mas Said students. The statistical analysis demonstrates a high level of significance (0.000) with a significance level of 5% (0.05), resulting in a p-value of 0.1329. Furthermore, all calculated values are less than the tabular values, affirming the validity of all questionnaire statements. In conclusion, this study reveals that Korean culture has made a substantial impact on the lifestyle of UIN Raden Mas Said students, with positive outcomes. The findings contribute to a comprehensive understanding of the influence of foreign cultures on the younger generation, highlighting both the advantages and potential challenges they pose within the context of family education and contemporary society.